Falling Out of Love: Divorce of Three Acehnese Ubanan Couples in the Islamic Law Perspective - Husin, Asna (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
“The most hated of permissible things to Allāh the Exalted is divorce”—this Prophetic tradition is narrated by AbūDāwūd and Ibn Mājah. Yet divorce is now on the rise in Aceh where Islamic Sharī‘ah is supposedly being implemented; there were 6,823 divorce cases in the province during the first ten months of 2022, with most proposed by young couples. This study examines divorce in mature families aged fifty and above, who have been married for many years in the perspective of Islamic law. We analyze their marriage and the nature of their life leading to divorce, the reasons for falling out of love, and the impact of separation on their well-being and on their loved ones. We review the Islamic sources and academic literature about marriage and divorce, the government and media reports for statistics, and we interview three couples along with several of their children in order to obtain insights into their experience. We uncover the complexity surrounding marriage and divorce, as well as religious, social, and personal reasons guiding their action or non-action. The study recommends that governments and religious institutions implement premarital courses as a condition of marriage so that divorce rates can be reduced. Such policies must be accompanied by meaningful and well-funded national government programs to save the institution of marriage and be able to maintain family cohesion in Indonesia.